The Contribution of the Qur'an Mu'allimil Council (MMQ) in Qiraati Method Teacher Learning at Al Qur'an Education Park - Silviya Indriyani; Ainun Nadlif (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the contribution of the Majlis Mu'allimil Qur'an (MMQ) in the Qiraati method teacher learning at TPQ Tuhfatul Athfal Krembung Sidoarjo. In this study using a descriptive qualitative method. In this case, the research subject is the teacher of the Qiraati method at TPQ Tuhfatul Athfal Krembung Sidoarjo. Data collection techniques are interviews, observation, and documentation. The analysis technique uses data reduction, data presentation, and conclusions. The results of this study indicate that the contribution of the Majlis Mu'allimil Qur'an (MMQ) in the Qiraati method teacher learning at TPQ Tuhfatul Athfal Krembung Sidoarjo is very useful because it can maintain the reading of the Qur'an, add insight into Qiraati's, and improve quality of learning. The supporting factors are good family factors, strong intentions, activeness and enthusiasm, commitment to progress and success, and perseverance to practice. While the inhibiting factors in this study were teacher absences, teacher delays, time delays, and timing.